Timing and approaches in congenital cataract surgery: a randomised controlled trial. (October 2016) - Chen, Weirong; Long, Erping; Chen, Jingjing; Liu, Zhenzhen; Lin, Zhuoling; Cao, Qianzhong; Wu, Xiaohang; Wang, Qiwei; Lin, Duoru; Li, Xiaoyan; Luo, Lixia; Qu, Bo; et al.
Abstract: Background: The optimum timing of surgery and the approach that should be used during congenital cataract surgery are controversial and present challenges for paediatric cataract surgeons in China. The aim of this study was to compare visual prognoses and postoperative adverse effects of paediatric cataract surgery done at different times and using different surgical approaches. Methods: In this prospective, randomised controlled trial, we recruited Chinese patients aged 3 months or younger who were diagnosed with bilateral diffuse or total cataracts, but who did not have coexisting ocular, systemic or neurological diseases. Patients were randomly assigned into two surgical timing groups: a 3-month-old and a 6-month-old. Each eye had one of three randomly assigned surgical procedures: lens aspiration, lens aspiration with posterior continuous curvilinear capsulorhexis, and lens aspiration with posterior continuous curvilinear capsulorhexis and anterior vitrectomy. Long-term visual acuity and incidence of postoperative secondary glaucoma and severe posterior capsular opacification were the primary outcomes. χ 2 tests, Fisher's exact tests and Kruskal-Wallis tests were used to compare the outcomes between groups. Generalised Estimating Equation with a working covariance matrix of unstructured correlations was integrated into the multivariate linear regression to explore the relationship between long-term visual acuity and the incidence of complications. The research protocol was approved by the Institutional Review Board and Ethics Committee of Sun Yat-sen University. Informed written consent was obtained from at least one family member of each participating patient, and the study was done according to the Declaration of Helsinki. This trial is registered withClinicalTrials.gov, numberNCT02581046 . Findings: We recruited 61 patients (30 girls, 31 boys) to our study. 4 children were excluded from the final analysis because their parents declined participation. A total of 57 participants (114 eyes) with a mean follow-up of 48·7 months were included in the final analysis. Long-term visual acuity in patients who underwent surgery aged 6 months (0·81 [SD 0·28]) was better than that of patients who had surgery aged 3 months (0·96 [0·30], p=0·02) and incidence of posterior capsular opacification during the 6 months following surgery was positively correlated with long-term visual acuity (β=-0·080, p=0·036). Two (2/95, 2%) eyes with a confirmed diagnosis of secondary glaucoma were in the 3-month-old group, and additional surgical interventions were done in these patients to lower the intraocular pressure. For patients who had surgery aged 6 months, the incidence of severe posterior capsular opacification was significantly higher in the lens aspiration group than other two groups (lens aspiration, 8/15 [53%]; lens aspiration with posterior continuous curvilinear capsulorhexis, 3/21 [14%]; and lens aspiration with posterior continuous curvilinear capsulorhexis and anterior vitrectomy, 3/16 [19%]; p=0·03). Interpretation: It was safer and more effective for Chinese bilateral diffuse congenital cataract patients to have surgery of lens aspiration with posterior continuous curvilinear capsulorhexis with or without anterior vitrectomy at 6 months of age than at 3 months of age. Funding: National Basic Research Program (973; 2015CB964600); Natural Science Foundation of Guangzhou (91546101, 81300750); Clinical Research and Translational Medical Center for Pediatric Cataract in Guangzhou, China.